Cultivo do melão sob diferentes frequências de irrigação e parcelamento da adubação nitrogenada no Vale do Curu, CE - Pereira Filho, João Valdenor (2012)
The melon has recognized the socio-economic status in northeastern Brazil, and the studies that define the appropriate irrigation frequency and timing of nitrogen application the melon are essential, as they can considerably improve the yield and fruit quality. Thus, the experiment was conducted during the months from July to October 2011 with the objective of evaluating the behavior of melon grown under different irrigation frequencies and under the effect of split nitrogen fertilization at different times. The study was conducted at the Fazenda Experimental Vale Curu, Pentecoste, Ceará, Brazil. The experimental design was that of randomized blocks with split plots. The treatments were combinations of six irrigation frequencies: F1 – 2.0 day-1; F2 – 1.0 day-1; F3 - 0,5 day-1; F4 - 0,3 day-1; F5 - 0,25 day-1 e F6 - 0,2 day-1 and four ways of applying 90 kg N ha-1 : 100% at 20 days after sowing (DAS) - (0-100-0-0); 30% at sowing and 70% at 20 DAS - (30-70-0-0); 30% at sowing, 30% at 20 DAS and 40% at 35 DAS (30-30-40-0); 20% at sowing, 30% at 20 DAS, 30% at 35 DAS and 20% at 50 DAS (20-30-30-20). It was found that the more frequent irrigations, as well as the application of nitrogen topdressing up to 50 DAS result in better culture growth, which greater main stem length, more leaves, greater stem diameter, more dry leaf mass, more dry stem mass and more total dry mass. As for the physiological characteristics (stomatal conductance, photosynthesis and transpiration) daily irrigation frequency (F2) produced the best results. There was no significant interference of the photosynthesis varable on the effects of split nitrogen fertilization. Regarding the characteristics of fruit quality, the highest frequencies of irrigation promoted the best of fruit by the Brix and total acidity criteria. The pH of the fruits, however, was not influenced by irrigation. Under water deficit conditions the fruits had the highest rate of maturation (rate). We observed larger fruit and better fruit shape index, larger mean weight and higher total yield potential under high frequency irrigation. The highest yield potential was obtained with the F2 treatment (daily irrigation) with 18846.80 kg ha-1. As to the partitioning of the nitrogen fertilizer, the topdressing application of N fertilizer up to 35 DAS provided fruits with the largest average mass.